Energy system contributions and determinants of performance in sprint cross-country skiing - Andersson, E.; Björklund, G.; Holmberg, H. C.; Ørtenblad, N. (Scandinavian Journal of Medicine & Science in Sports, 2017)
To improve current understanding of energy contributions and determinants of sprint-skiing performance, 11 well-trained male cross-country skiers were tested in the laboratory for VO2max, submaximal gross efficiency (GE), maximal roller skiing velocity, and sprint time-trial (STT) performance. The STT was repeated four times on a 1300-m simulated sprint course including three flat (1°) double poling (DP) sections interspersed with two uphill (7°) diagonal stride (DS) sections. Treadmill velocity and VO2 were monitored continuously during the four STTs and data were averaged. Supramaximal GE during the STT was predicted from the submaximal relationships for GE against velocity and incline, allowing computation of metabolic rate and O2 deficit. The skiers completed the STT in 232 ± 10 s (distributed as 55 ± 3% DP and 45 ± 3% DS) with a mean power output of 324 ± 26 W. The anaerobic energy contribution was 18 ± 5%, with an accumulated O2 deficit of 45 ± 13 mL/kg. Block-wise multiple regression revealed that VO2, O2 deficit, and GE explained 30%, 15%, and 53% of the variance in STT time, respectively (all P < 0.05). This novel GE-based method of estimating the O2 deficit in simulated sprint-skiing has demonstrated an anaerobic energy contribution of 18%, with GE being the strongest predictor of performance